A qualitative investigation of decision making during help-seeking for adult hearing loss. (1st November 2016) - Pryce, Helen; Hall, Amanda; Laplante-Lévesque, Ariane; Clark, Elizabeth
Abstract: Objective: The Any Qualified Provider framework in the National Health Service has changed the way adult audiology services are offered in England. Under the new rules, patients are being offered a choice in geographical location and audiology provider. This study aimed to explore how choices in treatment are presented and to identify what information patients need when they are seeking help with hearing loss. Design: This study adopted qualitative methods of ethnographic observations and focus group interviews to identify information needed prior to, and during, help-seeking. Observational data and focus group data were analysed using the constant comparison method of grounded theory. Study sample: Participants were recruited from a community Health and Social Care Trust in the west of England. This service incorporates both an Audiology and a Hearing Therapy service. Twenty seven participants were involved in focus groups or interviews. Results: Participants receive little information beyond the detail of hearing aids. Participants report little information that was not directly related to uptake of hearing aids. Conclusions: Participant preferences were not explored and limited information resulted in decisions that were clinician-led. The gaps in information reflect previous data on clinician communication and highlight the need for consistent information on a range of interventions to manage hearing loss.